Delayed Gastric Emptying of Semi-solid diets in Patients with Chagasic Megaesophagus - Chinzon,Decio (2014)
OBJECTIVE: To measure the time to gastric emptying of a semi-solid diet in individuals with Chagasic megaesophagus, in comparison with a non-Chagasic control group. METHOD: The time to gastric emptying of a semi-solid diet was assessed via ultrasonography in 28 patients with Chagasic megaesophagus (grades I, II, and III) and compared to that of a control group (n = 15). After measurement of antral diameter under fasting conditions, 400mL of a semi-solid diet were administered and consecutive measurements were performed every 30 min. RESULTS: The duration of dysphagia was significantly lower in patients with megaesophagus grade I than in those with grades II or III. The time to gastric emptying was significantly increased in the megaesophagus group compared to the control group. The means of antral areas measured under fasting conditions and after maximal antral distension did not differ between the megaesophagus and control groups. CONCLUSION: The time to gastric emptying of a semi-solid diet was significantly greater in patients with Chagasic megaesophagus than in controls. The delay did not depend on the extent of dilatation of the megaesophagus or the duration of dysphagia.